(untitled) (Slavic Studies, 2024)
The analysis in this paper is concerned with the investigation of the medieval literary and cultural heritage as an essential element and precondition which determines the development of Macedonian literature towards more contemporary forms. The analysis focuses of the 19th century literary phenomena in Macedonia, which are generically and stylistically related to certain Slavic works (mainly the genre discourse and the adaptation of its stylistic properties in accordance to Slavic literary tradition). The correlation with culturally similar ways of writing is also taken into account (the translation of the texts of Damaskinos Stouditis), as well as the modes of expression and writing in the texts originating from the 19th century in Macedonia, thus reevaluating their connectedness. The changes in the literary system through the eras are also taken into consideration, especially in Grigor Prlichev’s discourses, since they are a proper example of the way medieval tradition is functionally upgraded by outgrowing simple recognition of the names and works of the founders of Slavic tradition.